An analysis of profitability determinants in Chinese commercial banks - Song, Lingkai (2018)
Through annual figures from 162 active Chinese commercial banks from 2012 through 2017, this paper uses economic growth and industry concentration as prospective external factors together with cost efficiency, capital adequacy, various aspects of risk management, bank size, earning stability, and revenue diversification as prospective internal factors to investigate how these factors affect bank profitability. In the first step, we estimate cost efficiency score for each chosen bank during the examined period via Stochastic Frontier Analysis (SFA). From the initial point of 92.68%, the efficiency level demonstrates a downward trend until it hits the lowest point in 2016, although it rebounds to the initial point in 2017. As regards types of ownership, joint-stock commercial banks stand out as the most efficient bank type. Then, cost efficiency derived from the first stage is incorporated in the system Generalized Method of Moment (SGMM) as endogenous regressor. The result reveals that Chinese bank profitability is greatly affected by cost efficiency, risk-taking behaviours, earning stability together with external factors such as GDP growth and market concentration.